Elevated Plasma Growth and Differentiation Factor 15 Is Associated With Slower Gait Speed and Lower Physical Performance in Healthy Community-Dwelling Adults. (15th March 2019) - Semba, Richard D; Gonzalez-Freire, Marta; Tanaka, Toshiko; Biancotto, Angelique; Zhang, Pingbo; Shardell, Michelle; Moaddel, Ruin; ,; Ferrucci, Luigi
Abstract: Background: Growth and differentiation factor 15 (GDF-15) has been associated with obesity, muscle wasting, and cachexia. The receptor for GDF-15 was recently identified in the brainstem and regulates food intake and metabolism. The relationship of plasma GDF-15 with the age-associated decline of muscle mass and strength, gait speed, and physical performance in adults has not been well characterized. Methods: Plasma GDF-15, grip strength, 6-m gait speed, 400-m walking test time, lower extremity physical performance score, appendicular lean mass, and fat mass were measured in 194 healthy adult participants, aged 22–93 years, of the Baltimore Longitudinal Study of Aging. Results: Plasma GDF-15 concentrations increased with age ( p < .001) and were higher in whites compared with blacks and Asians ( p = .04). Adults with higher plasma GDF-15 had slower 6-m gait speed, longer 400-m walking time, and lower physical performance score in multivariable analyses adjusting for age and race. Plasma GDF-15 was not associated with grip strength, appendicular lean mass, or fat mass. Conclusions: Elevated plasma GDF-15 is associated with slower gait speed, higher 400-m walking time, and lower physical performance in very healthy community-dwelling adults. The relationship between plasma GDF-15 and sarcopenia-related outcomes may be stronger in the population not selected to be healthy, and this hypothesis should be tested in a representative population.